2017
DOI: 10.1021/acsami.7b03074
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Amphiphilic Block Copolymers/CdTe Nanocrystals for Efficient Aqueous-Processed Hybrid Solar Cells

Abstract: Due to their low cost and high efficiency, polymer/nanocrystal hybrid solar cells (HSCs) have attracted much attention in recent years. In this work, water-soluble hybrid materials consisting of amphiphilic block copolymers (ABCPs) and cadmium telluride nanocrystals (CdTe NCs) were used as the active layer to fabricate the HSCs via aqueous processing. The ABCPs composed of poly(3-hexylthiophene) (P3HT) and poly(acrylic acid) (PAA) self-assembled into ordered nanostructured micelles which then transformed to na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…[31,32] As shown in Figure 4d, the decay dynamics of ZnO:CdTe film are faster, which means better electron extraction efficiency compared with TiO 2 :CdTe films. [2,5,[7][8][9]13,15,17,[33][34][35][36][37][38][39][40] It is shown that the highest PCE (6.51%) and J sc (19.5 mA cm −2 ) have been obtained in this work. As a result, the probability of carrier recombination process becomes smaller.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…[31,32] As shown in Figure 4d, the decay dynamics of ZnO:CdTe film are faster, which means better electron extraction efficiency compared with TiO 2 :CdTe films. [2,5,[7][8][9]13,15,17,[33][34][35][36][37][38][39][40] It is shown that the highest PCE (6.51%) and J sc (19.5 mA cm −2 ) have been obtained in this work. As a result, the probability of carrier recombination process becomes smaller.…”
mentioning
confidence: 54%
“…In addition, the PCE and J sc in this work are compared with those previously published articles based on AHSC (Figure 5) and other performance parameter values are shown in Table S4 in the Supporting Information. [2,5,[7][8][9]13,15,17,[33][34][35][36][37][38][39][40] It is shown that the highest PCE (6.51%) and J sc (19.5 mA cm −2 ) have been obtained in this work.…”
Section: Hybrid Solar Cellsmentioning
confidence: 99%
“…[43][44][45][46][47] Severalr eview articles have been published on different strategies to improve the performance of lab-scale PSCs. [48][49][50][51][52][53][54][55][56][57] As it is typical for novel technologies, [58][59][60][61][62] research in the field of PSCs is currently focusedo no vercoming important issues, starting from the difficulty of reproducing high power conversion efficiency (PCE) values when the devicea rea is increaseda tt he module level. Secondly,t he selection of cell components must be reconsidered thinking at al arge-scale commercialization because some of the standard materials (like HTMs)c urrently used in lab-scale devices have unrealistic costs for at hird generation photovoltaict echnology.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, spherical crystalline micelles basically have no growth process and two‐dimensional lamellar micelles grow along four directions. The cylindrical micelles of BCPs also have a wide range of potential applications in various fields, including optoelectronic materials, catalysis and biomedical materials . The high aspect ratio of cylindrical micelles is advantageous to applications under some situations, as compared with the micelles with other morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The cylindrical micelles of BCPs also have a wide range of potential applications in various fields, including optoelectronic materials, catalysis and biomedical materials. [78][79][80][81][82][83][84][85][86][87] The high aspect ratio of cylindrical micelles is advantageous to applications under some situations, as compared with the micelles with other morphologies. For instance, worm-like micelles can toughen epoxy resin more effectively, [88] and conductive network can be formed more easily when cylindrical micelles with a conjugated core-forming block are used as filler.…”
Section: Introductionmentioning
confidence: 99%